KEWENANGAN PEMERINTAH KABUPATEN/KOTA DALAM BIDANG PERTANAHAN* - Urip Santoso (Jurnal ADIL, 2015)
AbstractThe Law No. 5 of 1960 on National Agrarian Law explicitly stipulates that the authority in agrarian issues is the property of the State (Central Government). However, this authority—as stipulated in the Presidential Decree PP No. 38 2007—is transferable from the Central Government to Local Governments. The Law specifies 9 features of agrarian authorities which are transferable to municipal governments. In this respect, the National Land Agency (BPN) is the authorized body which is in charge of the agrarian registration-related matters.Keywords : Authority, Local Government, AgrarianAbstrakDalam Hukum Tanah Nasional yang diatur dalam undang-undang No. 5 Tahun 1960, secara tersirat ditetapkan bahwa Kewenangan di bidang Pertanahan merupakan Kewanangan Pemerintah Pusat. Kewenangan tersebut dapat dilimpahkan kepada Pemerintah Daerah dalam PP No. 38 Tahun 2007 ditetapkan bahwa ada 9 kewenangan di bidang Pertanahan yang di serahkan kepada Pemerintah Kabupaten/Kota. Kewenangan di bidang Pendaftaran Tanah tetap dilaksanakan oleh Badan Pertanahan Nasional.Kata Kunci : Kewenangan, Pemerintah Daerah, Pertanahan